A safer way to search disaster sites. - Weston, J. (IEEE Robotics and automation magazine)
North Carolina State University engineers design a pipe-crawling robot to help save lives. Two versions of the modular observation crawler and sensing instrument: MOCASIn I and MOCASIn II, which are robots that can crawl through six-inch piping, have been developed